Effect of plant spacing and number of suckers on yield components and fruit quality of the plant crop and the first four ratoons of banana clones in central Sudan - Mahmoud, Haroun; Elkashif, Mohamed; Elamin, Osman (Gezira Journal of Agricultural Science; Vol 9 No 1 (2011), 2011)
Experiments were carried out at the research farm of the National Institute for the Promotion of Horticultural Exports (NIPHE), University of Gezira, Wad Madani, Sudan, during the period from January 2001 to April 2004 to study the effects of plant spacing and number of suckers on crop cycles, yield and fruit quality of the plant crop and the first four ratoons of introduced banana clones, namely William's Hybrid 172 (WH) and Grand Nain 1824 (GN) in comparison with the local clone Dwarf Cavendish (DC). Plant spacing was 2x2 m, 2x3 m and 3x3 m. The selected suckers were 2, 3, or 4 around the mother plant. Treatments were arranged in a split-split plot design with three replications. The introduced clones GN and WH produced significantly higher bunch weight, total and exportable yields and longer fruit green life, but lower total soluble solids (TSS) content than the local clone DC in the plant crop and ratoons. Plant spacing of 3x3 m resulted in the highest bunch weight and exportable yield, but it gave the lowest total yield in both the plant crop and ratoons as compared to the close spacing of 2x2 m. Also, the wide spacing resulted in significantly shorter crop cycles, longer fruit green life and higher TSS content than the close spacing. Keeping two suckers per mat resulted in the highest bunch weight and the highest exportable and total yields in the plant crop and ratoons, but longer crop cycles. However, keeping four suckers per mat produced the lowest total and exportable yields, but resulted in shorter crop cycles.      أجريت هذه التجارب بمزرعة بحوث المعهد القومي لتنمية الصادرات البستانية جامعة الجزيرة , السودان في الفترة من يناير 2001 إلي ابريل 2004م لدراسة تأثير مسافات الزراعة وعدد الخلف على الإنتاجية ودورة المحصول وجودة الثمار للمحصول الأم والأربعة خلف التالية لبعض السلالات المستجلبة من الموز وهي  هجين و ليم 172 والجراند نين 1824 مقارنة بالصنف المحلي الكافندش القزم. أبعاد الزراعة كانت كالآتي: 2x 2 م و23x م وx33 م. عدد الخلف 2،3 أو 4 خلفه حول النبات الأم. صممت التجربة علي نسق استخدام التصميم المنشق بثلاثة مكررات.  أعطت السلالات المستجلبة من خارج السودان GN و WH أعلى أوزان للسبائط وأعلى الإنتاجية الكلية وكذلك الإنتاجية القابلة للتصدير بالمقارنة مع السلالة المحلية DC، في النبات الأم والأربعة خلف الأولى. كذلك أعطت السلالات المستجلبة أطول فترة للعمر الأخضر للثمار ولكنها أعطت أقل محتوى من المواد الصلبة  الذائبة مقارنة بالسلالة المحلية DC. زراعة الموز بأبعاد 3 x 3 متر أعطت أعلى أوزان للسبائط وأعلى إنتاجية للموز القابل للتصدير ولكن الإنتاج الكلي كان أقل بالمقارنة مع الزراعة في أبعاد 2 x 2 متر، وذلك في النبات الم والأربعة خلف التالية. كذلك أعطت الزراعة في أبعاد 3 x 3 متر أطول فترة للعمر الأخضر للثمار وأعلى محتوى من المواد الصلبة الذائبة مقارنة بالزراعة المتقاربة. أعطت الزراعة المتقاربة (2 x 2  متر) دورة محصولية أطول بالمقارنة مع الزراعة المتباعدة  (3 x 3 متر). عند ترك خلفتين مع النبات الأم، أدى ذلك إلى أعلى أوزان للسبائط وأعلى إنتاجية كلية وأعلى إنتاجية من الموز القابل للتصدير وأطول دورة محصولية في النبات الأم والخلف الأربعة التالية، وذلك بالمقارنة مع ترك أربعة خلف مع النبات الأم.